The Influence of E-Commerce and E-Payment on Purchasing Decisions - Widi Astuti; Diansyah Diansyah (Resolusi: Jurnal Sosial Politik, 2022)
One aspect that can lead to consumer purchasing decisions is the influence of information in electronic or online media. The information in such media is more effective compared to the ones in social life. The electronic media have greater accessibility and greater reach since consumers use online media with the aim of sharing their own experiences to a brand, product, or service that they have experienced. In the case of fashion model, the consumers use electronic commerce (e-commerce) electronic payment (e-payment) for purchasing. Using the fashion model as a moderating variable, this study shows that e-commerce has a positive and significant impact on purchasing decisions. At the same time, e-payment has a positive and significant effect, fashion models have a positive and significant effect.